2-DIMENSIONAL GEL ELECTROPHORESIS PROFILES OF HEMOLYMPH OF HORSESHOE CRABS TACHYPLEUS GIGAS AND CARCINOSCORPRIUS ROTUNDICAUDA - DASH, BISNU PRASAD; PATI, SIDDHARTH; MOHANTY, BIMAL PRASANNA; MAHANTY, ARABINDA (Journal of the Inland Fisheries Society of India, 2021)
Horseshoe crabs are members of the Limulidae family and are considered 'living fossils' as these have undergone very little change from their fossilized ancestors in the last 450 million years (Kin and Błażejowski 2014). Presently, four species of horseshoe crabs are found in the world. The Atlantic horseshoe crab Limuluspolyphemus and the Asian horseshoe crabs Tachypleus gigas, Tachypleus tridentatus, and Carcinoscorpius rotundicauda out of which Tachypleus gigas and Carcinoscorprius rotundicauda are found in the coast of Balasore, Odisha (Pati et al., 2015; Pati and Dash 2016). While the biology of the Atlantic HorseshoeLimulus polyphemus has been extensively studied and its blood (hemolymph) has found a number of medical applications, very less studies have been carried out on its Asian counterparts. In this context, a preliminary study has beencarried out to generate the one and two-dimensional gel electrophoresis profiles of the hemolymph proteins of Tachypleus gigas and Carcinoscorprius rotundicauda.